Graphene patterning without plasma etching via SU-8 pattern peel-off - Maryam Riyahi; Gholam-Mohammad Parsanasab; Mohammad Sabaeian (Scientific Reports)
Abstract Although graphene has made its way into many areas of science and technology, proper tools for patterning graphene are not available to all researchers. Therefore, any new patterning method is useful. This research investigates the patterning of graphene layers on $${{Si{O_2}} \mathord{\left/ {\vphantom {{Si{O_2}} Si}} \right. \kern-0pt} Si}$$ substrates via the use of an SU-8 photoresist to produce micrometer-sized components such as electrodes. The new method is based on the sufficient adhesion of graphene to SU-8 after SU-8 cross-linking. First, SU-8 photolithography in the inverse form of the final pattern is carried out on the graphene layer. Then, both the SU-8 pattern and the graphene part attached to it are simultaneously removed, resulting in the final graphene pattern. This method can also be extended in a way that is compatible with imprint lithography, as its framework is described in this paper. In this way, the non-crosslinked SU-8 in the inverse pattern is transferred to the graphene layer via a premade stamp. This latter approach could benefit from the complete elimination of SU-8 effects, especially SU-8 contamination, from the final graphene pattern, as well as the simplicity of replication for mass production.